(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The present work analyzes the gamification of the evaluative proposal elaborated during the year 2020 in the Laboratory I subject belonging to the Bachelor of Electronic Arts of the National University of Tres de Febrero (UNTREF). This laboratory is presented as an initial curricular space whose main purpose is to offer an introduction to electronic arts, creative programming and artistic experimentation. The evaluative proposal, called Odyssey L120: the virtual experience, was developed as a way to overcome the following problems: the creative block before the realization of an artistic project in an initial instance of a university career; the isolation product of the health emergency by COVID-19; the adequacy based on the time needed to carry out the project; and coherence with the contents and methodology worked on in the course. The proposal involved the realization of a digital card reading with different elements -visual, material, sound and textual- that worked as triggers to create an artistic production for the end of the course. The mechanics of the game were structured based on a science fiction narrative, a set of rules and a collaborative dynamic between the participants. The experience result shows great motivation among the students and a particular focus on collaborative work as a result of the network system. Among the main conclusions, it is established that the strategies of the game -both the opening of possibilities and the imposition of limits- are valuable to structure instances of artistic creation.